Alternative prioritization for mitigating competition-related issues in Tanzania sugar industry using an integrated multi-criteria decision-making approach - Tafuteni Nicholaus Chusi; Yu Zuo; Azam Shehbaz; Mouhamed Bayane Bouraima (Heliyon)
Professionals and policymakers often encounter challenges in selecting and ranking effective solutions to address competition-related issues in various industries including sugar industry. Despite extensive research in this area, the Tanzanian context, significantly impacted by these challenges, has not received sufficient attention. Thus, this study aims to fill this gap by identifying and prioritizing these issues. It proposes four strategies and establishes five criteria for prioritization. To achieve this, the study introduces an integrated methodology to assess criteria weights and rank strategies based on these weighted criteria. The FullEX technique is applied to assess the criteria weights, while the AROMAN (Alternative Ranking Order Method Accounting for Two-Step Normalization) method is used to rank the alternatives. The study validates this methodology through a sensitivity and comparative analyses, which identifies the amendment of the law to accommodate the leniency program (S1) as the most appropriate strategy for mitigating competition-related issues in the sugar industry.